1986
DOI: 10.1111/j.1751-1097.1986.tb05592.x
|View full text |Cite
|
Sign up to set email alerts
|

AN ACTION SPECTRUM FOR BLUE AND NEAR ULTRAVIOLET IN ACTIVATION OF Propionibacterium acnes; WITH EMPHASIS ON A POSSIBLE PORPHYRIN PHOTOSENSITIZATION

Abstract: —Propionibacterium acnes (P. acnes), grown on Eagles medium with different pH. were irradiated with monochromatic light in the range 320 to 440 nm. Different pH leads to different porphyrin concentrations in the cells. The light sensitivity of the bacteria was estimated from the reduction in their ability to form colonies after radiation. The sensitivity was highest for the lowest wavelength (320 nm). and decreased continuously with increasing wavelength up to 380 nm. In the region between 380 and 440 nm there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 22 publications
3
72
0
Order By: Relevance
“…Bacteria of the strain Propionibacterium were found to accumulate significantly more HPD than did the other strains tested. Propionibacterium acnes also produces porphyrins endogeneously, mainly PP and CP (Kjeldstad et al, 1984). The production was found to be pH-dependent with an optimum at pH 6.1.…”
Section: Sensitization Of Microorganisms Cells and Organellesmentioning
confidence: 96%
“…Bacteria of the strain Propionibacterium were found to accumulate significantly more HPD than did the other strains tested. Propionibacterium acnes also produces porphyrins endogeneously, mainly PP and CP (Kjeldstad et al, 1984). The production was found to be pH-dependent with an optimum at pH 6.1.…”
Section: Sensitization Of Microorganisms Cells and Organellesmentioning
confidence: 96%
“…This reaction stimulates production of reactive free radicals and singlet oxygen species, which results in destruction of the bacteria [14][15][16][17][18][19][20][21][22][23]. Although the bacterial sensitivity to light becomes higher as the wavelength gets shorter, there exists a second absorption peak at 415 nm, which corresponds to that of coproporphyrin III, the predominant bacterial porphyrin produced by P. acnes [15,21,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been revealed that visible light activates the endogenous porphyrins of P. acnes, which results in a photodynamic reaction to destroy the bacteria [14][15][16][17][18][19][20][21][22][23]. The absorption peak of the bacterial porphyrins is at 415 nm, which falls into the blue light waveband [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been known that natural light allows reducing acne intensity: firstly, ultraviolet radiation has bactericidal effect; secondly, it suppresses skin inflammatory processes [27,28]. Data of these trials stimulated development of new methods of acne treatment with lasers and other light sources.…”
Section: Physiotherapeutic Methods Of Acne Treatmentmentioning
confidence: 99%